Study of the Adsorption Mechanism and the Structure of Adsorbed Layers of Polyelectrolytes at the Metal Oxide/Solution Interface - S. Chibowski; M. Wiśniewska (Adsorption Science & Technology)
The influence of the molecular weight of polyacrylic acid (PAA) and polyacrylamide (PAM) as well as of inorganic contaminants on the ZrO 2 surface on the adsorption and electrokinetic properties of the metal oxide/polyelectrolyte solution interface were studied for ZrO 2 and Fe 2 O 3 solid particles. The calculated concentrations of the various surface groups on ZrO 2 and Fe 2 O 3 enabled an investigation of the possible mechanism for the bonding of the studied polyelectrolytes with the surfaces of both oxides. PAA and PAM macromolecules bond with the solid surface mainly via the –OH groups of the oxides, which may interact with the carboxy groups of polyelectrolytes through hydrogen bridging. A comparison of the change in values of the diffuse layer charge with the surface charge enabled the principal factors responsible for the changes in the zeta potential of the oxides, e.g. pH, polymer molecular weight and concentration of the polymer solutions, to be evaluated. From such zeta potential values, it was possible to determine the free energies of adsorption of PAA and PAM on the surfaces of both oxides. The thicknesses of adsorbed polymer layers on Fe 2 O 3 and ZrO 2 were calculated on the basis of measurements of their suspension viscosities in the absence and presence of adsorbed polymer. It was shown that the thickness of the adsorption layer increased with increasing polymer molecular weight, pH and concentration of the polymer solution. Because the experimental determination of the number and the length of trains, loops and tails in such polyelectrolytes was not possible, the participation of such segments of polymer structure at the interface was computed using the Scheutjens–Fleer model of polymer adsorption. The polymer adsorption expressed as the number of equivalent monolayers was calculated and compared with the experimental data.